Synthesis, biological evaluations, and in silico assessments of phenylamino quinazolinones as tyrosinase inhibitors - Sara Moghadam Farid; Shahram Moradi Dehaghi; Aida Iraji; Mohammad Mahdavi; Mina Saeedi (Scientific Reports)
Abstract A series of novel phenylamino quinazolinone derivatives were designed and synthesized as potential tyrosinase inhibitors. Among these compounds, 9r emerged as the most potent derivative, exhibiting IC50 values of 17.02 ± 1.66 µM, compared to kojic acid as the positive control with an IC50 value of 27.56 ± 1.27 µM. Antioxidant assessment of 9r compounds showed 24.67% inhibition at 100 µM. Molecular docking studies of these derivatives were conducted, revealing their proper fitting within the enzyme’s active site. Additionally, density functional theory analysis was performed on the potent derivatives, indicating their stability and reactivity. Notably, the highest values of the energy gap were observed in 9r and 9s derivatives, underscoring their potential efficacy. Further kinetic studies of compound 9r, identified as the most potent derivative, demonstrated a competitive mode of inhibition with a K i value of 14.87 µM. Molecular dynamics simulations of the 9r-tyrosinase complex revealed stability over time, with a reduction in critical residual fluctuation during the simulation. Overall, these findings contribute to a deeper understanding of the potential therapeutic value of these derivatives as tyrosinase inhibitors.